An examination of relational dynamics of power in the context of supported (assisted) decision‐making with older people and those with disabilities in an acute healthcare setting - Deirdre O'Donnell; Carmel Davies; Lauren Christophers; Éidín Ní Shé; Sarah Donnelly; Thilo Kroll (Wiley, 2023)
Abstract Introduction Supported (assisted) healthcare decision‐making (ADM) focuses attention on how people with disabilities, including cognitive impairments, can be best supported to make decisions about their health and social care on an equitable basis with others. Meaningful implementation of legal frameworks for ADM challenges long‐held presumptions about who has access to valued decision‐making resources, influence and power within a particular socio‐cultural setting. This study aims to explore the relational power dynamics around ADM with older people in acute care settings. Methods This study adopts a critical hermeneutic approach to qualitatively explore the lived experience of ADM from the perspectives of Health and Social Care Professionals (N = 26). This is supported by an exploration of the experiences of older people (N = 4), older people with a diagnosis of dementia (N = 4) and family carers (N = 5). Results We present three themes of data analysis that represent three spaces where the relational aspects of power in ADM are manifested. The first space, centralising decision‐making power within multidisciplinary teams identified the privileging of physicians in traditional hierarchical leadership models that may lead to the implicit exclusion of family carers and some Health and Social Care Professionals in the ADM process. Privileging cognitive and communication competence identified a tendency to attribute decision‐making autonomy to those with cognitive and communication competency. The final space, balancing the duty of care and individual autonomy, recognises acute care settings as typically risk‐averse cultures that limit autonomy for decisions that carry risk, especially for those with cognitive impairment. Conclusion Findings indicate the need to address cultural sources of power operating through social norms premised on ageist and ableist ideologies. It is necessary to challenge institutional barriers to meaningful ADM including positional power that is associated with hierarchies of influence and protectionism. Finally, meaningful ADM requires resistance to the disempowerment created by structural, economic and social circumstances which limit choices for decision‐making. Patient or Public Contribution A public and patient involvement panel of older people were consulted in the development of the grant application (HRB: APA‐2016‐1878). Representatives from Alzheimer's Society Ireland and Family Carers Ireland were steering committee members guiding design and strategy.